"Simply not comprehensible." Why?. Issue 5 (July 2020) - Simon, Sven; Rathke, Hannes
Abstract: The German Federal Constitutional Court's ruling of May 5, 2020 on the ECB's Public Sector Purchase Programme (PSPP) stated, for the first time ever, that some decisions by European institutions are not covered by the competence allocations of the European Treaties and cannot therefore take effect in Germany. This article argues that the judgment came as no surprise, as it is consistent with the principle of conferral of powers. According to this principle the EU and its institutions can only act within the limits of their competences. The German Basic Law prohibits any transfer of sovereign rights whose exercise would confer sua sponte additional competences to the supranational level. Against this background, the Federal Constitutional Court judgment does not seek to limit the ECB's scope for appraisal and evaluation in the exercise of its monetary policy mandate. It focuses rather on the conditions which legitimize the ECB's leeway. The issue in this case is not the applicability of the proportionality principle as a criterion governing the delimitation of powers, but the different reference points for the assessment of proportionality. In this regard the CJEU had failed to discuss whether monetary policy and the effects on economic policy are proportionate by themselves. Hence, in constitutional terms, the CJEU's interpretation was found to be "arbitrary", since the German Constitutional Court defined arbitrariness as jurisprudence that "in a reasonable reading … [appears] unintelligible and clearly untenable." In other words, it is "simply not comprehensible." Despite the harsh words of the German Constitutional Court, the authors argue that the judgement in the end can help to create a European legal culture that will strengthen the European Union in the long term if, in future, the CJEU engages more constructively with criticisms from Member State courts.